Limited Liability in Corporate Group: A Critical Examination under Common Law and Shariah in Malaysia - Ramli, Nazri; Abd Ghadas, Zuhairah Ariff; Abd Aziz, Hartinie (Yuridika, 2025)
Limited liability is a default rule in company law that protects shareholders from shifted-business risk in a company to external parties. Its application in the corporate group setting is heavily criticized for causing harm to the subsidiary’s creditors particularly. While this rule is proposed to be refined due to its rigidly unreasonable privilege and lack of justice, it becomes more complicated where the Shariah-compliant businesses have adopted this rule as their corporate structure. Despite this, the Malaysian company law recognizes the distinct legal personalities of entities within corporate group regardless their businesses are typically operated as a single entity. Contrastingly, limited liability is not established in Islamic business entities like sharikah (partnership) because the latter entails a single entity premised on a sharing-business risk among the partners. The study undertakes doctrinal analysis to examine the application of limited liability in corporate group under the Malaysian company law and compare it with the Shariah principles of sharikah. The study relies on the library-based research in collecting and gathering the data to support this methodology. The paper proposes to show whether the conventional rule of limited liability could be directly applied to group of companies operating Shariah-compliant businesses which supposedly comply its corporate structure with sharikah. The paper concludes that such direct application is untenable due to different natures and business structures. Examining this comparison is substantial to explore the essential of forming a new business model for Shariah-compliant corporate groups structured based on sharikah principles.